Origins of the Hussite uprising: the chronicle of Laurence of Březová (1414-1421) - Laurentius, von Březová (Routledge Medieval Translations, 2020)
"The 'Hussite Chronicle' is the most important single source for the events of the early Hussite movement. The author is Laurence of Březová (c.1370-c.1437), a member of the Czech lower nobility and a supporter of the Hussite creed. The movement arose as an initiative for religious and social reform in fifteenth-century Bohemia and was energized by the burning of the priest Jan Hus in 1415. Church and empire attempted to suppress the movement and raised five crusades against the dissenters. The chronicle offers to history and scholarship a nuanced understanding of what can be regarded as an essential component for a proper understanding of late medieval religion. It is also a considered account of aspects of the later crusades. This is the first English-language translation of the chronicle"--